Response of Anthracnose Disease Intensity in Red Chili Plants (Capsicuum annuum L.) to Several Types of Fungicide Active Ingredients: Respon Intensitas Penyakit Antraknosa Pada Tanaman Cabai Merah (Capsicuum annuum L.) Terhadap Beberapa Jenis Bahan Aktif Fungisida - Lestari, Safira Rizka; Hidayat, Nur (Journal of Applied Plant Technology, 2024)
Red chilies are one of the important horticultural products in Indonesia. One of the plant pest disease organisms which attack red chili plants is anthracnose disease caused by the fungus Colletotrichum capsici. Prevention of plant pest disease organisms, especially anthracnose disease by farmers is still oriented towards the use of pesticides. Evaluation of existing fungicides must be carried out so that possible negative impacts can be anticipated early. A Randomized Block Design was used with treatment of several types of functional active ingredients, namely Hexanocazole 50 g/L + Carbendazim 50 g/L (P1); Azoxystrobin 250 g/L (P2); Tebuconazole 430 g/L (P3); Indoxacarb 20% (P4); Simoxanil 20% (P5); Dimethomorph 50% (P6); Methyl-thiophanate 70% (P7); Mancozeb 80% (P8); Azocystrobin 200g/L + Difenoconazole 125 g/L (P9); and control or no active ingredient (P10). The results show that Simoxanil 20% fungicide has an efficacy level of more than 60% and is able to prevent the spread of C. capsici attacks in the field at a disease intensity percentage of 30%.